Mechanistic aspects in the photodynamic inactivation of Candida albicans sensitized by a dimethylaminopropoxy porphyrin and its equivalent with cationic intrinsic charges - Quiroga, Ezequiel Dario (2020)
Photocytotoxic effect induced by 5,10,15,20-tetrakis[4-(3-N,N-dimethylaminopropoxy)phenyl]porphyrin (TAPP) and 5,10,15,20-tetrakis[4-(3-N,N,N-trimethylaminepropoxy)phenyl]porphyrin (TAPP+4) was examined in Candida albicans to obtain information on the mechanism of photodynamic action and cell damage. For this purpose, the photokilling of the yeast was investigated under anoxic conditions and cell suspensions in D2O. Moreover, photoinactivation of C. albicans was evaluated in presence of reactive oxygen species scavengers, such as sodium azide and D-mannitol. The results indicated that singlet molecular oxygen was the main reactive species involved in cell damage. On the other hand, the binding and distribution of these porphyrins in the cells was observed by fluorescence microscopy. Morphological damage was studied by transmission electron microscopy (TEM), indicating modifications in the cell envelopment. Furthermore, deformed cells were observed after photoinactivation of C. albicans by toluidine blue staining. In addition, modifications in the cell envelope due to the photodynamic activity was found by scanning electron microscopy (SEM). Similar photodamage was observed with both porphyrin, which mainly produced alterations in the cell barriers that lead to the photoinactivation of C. albicans.